What Really Matters: The Effect of Covid-19 on the Factors of Life Satisfaction - Janacek, Julius (International Journal of Emerging Trends in Social Sciences, 2021)
This article investigates the effect of the Covid-19 pandemic on the structure of factors of life satisfaction in the city of Usti nad Labem, Czech Republic. The dataset is based on a questionnaire survey conducted in Usti nad Labem, Czech Republic. Subsequent data analysis is conducted using ordinal logistic regression models. The results show that the emergence of the pandemic had a significant impact on life satisfaction factors. Firstly, the importance of family came to the fore: being in a relationship or being married proved to be a significant factor of life satisfaction during the pandemic but not before the pandemic. Secondly, a negative association between drinking alcohol and life satisfaction emerged during the pandemic. Alcohol probably started to be the tool for stress relief. Thirdly, sport became a significant positive factor of women’s life satisfaction. Sport most likely became an effective way of keeping oneself in balance. Results indicate that during a difficult time period there are different ways of how to deal with it. In this way doing sports and drinking alcohol seem to be substitute activities.